Authorea
DOI: 10.22541/au.158775654.40277732
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of semicontinuous bioreactor production of biopharmaceuticals in transgenic rice cell suspension cultures

Abstract: Biopharmaceutical protein production using transgenic plant cell bioreactor processes offers advantages over microbial and mammalian cell culture platforms due to the ability to produce complex biologics, use of simple chemically-defined, animal component-free media, robustness of host cells, and biosafety. A disadvantage of plant cells from a traditional batch bioprocessing perspective is their slow growth rate which has motivated us to develop semicontinuous and/or perfusion processes. Although the economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…At the laboratory scale, we produced ~16 mg of rrBChE in a 2 L working volume during a 12-day batch run, corresponding to a volumetric productivity of 0.680 mg L −1 day −1 . A technoeconomic model developed for semicontinuous large-scale production (25 kg/year) of rrBChE (without kifunensine addition) at a higher volumetric productivity (1.5 mg L −1 day −1 ) showed that the process could be cost-effective with a cost-of-goods sold of ~$660/gram, less than 3% of the estimated cost of plasma-derived hBChE at ~$25,000/gram [ 54 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…At the laboratory scale, we produced ~16 mg of rrBChE in a 2 L working volume during a 12-day batch run, corresponding to a volumetric productivity of 0.680 mg L −1 day −1 . A technoeconomic model developed for semicontinuous large-scale production (25 kg/year) of rrBChE (without kifunensine addition) at a higher volumetric productivity (1.5 mg L −1 day −1 ) showed that the process could be cost-effective with a cost-of-goods sold of ~$660/gram, less than 3% of the estimated cost of plasma-derived hBChE at ~$25,000/gram [ 54 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%